Role of public relations practices in content management: the mediating role of new media platforms - Al Hadeed, Ali Yahya; Maysari, Ihsan; Aldroubi, Mohammad Mahmoud; Attar, Razaz Waheeb; Al Olaimat, Farhan; Habes, Mohammed (Frontiers in Sociology, 2024)
Public Relations practices are widely accompanied by communication and persuasion. Especially today, when new media platforms provide direct accessibility, communication through PR is more improved. This research focused on media organizations in the UAE, with a special consideration to their audience content management. The researchers applied case study method and selected a sample of n= 280 individuals from n= 12 media houses currently working in the UAE. Results obtained by the Structural Equation Modelling (SEM) revealed that, Media Organizations in the UAE pay a significant consideration to Public Relations practices (p> .000) and New Media adoption (p> .000). Besides Both these Public Relations practices (p> .000) and New Media adoption are also found as significantly focusing on Two-way Communication. Consequently, this Two-way Communication is significantly affecting the content Management among these organizations (p> .000), leading to design, evaluate, and alter the content that is acceptable and liked by their audiences. Thus, it is concluded that the media content and its management is not a simple task. Audience and Communication are two basic factors that play an important role in this regard. Further, the role of Public Relations practices also enhances the communication and content management practices, leading to even more constructive outcomes.